Rainfall leads to elevated levels of antibiotic resistance genes within seawater at an Australian beach. (15th August 2022) - Williams, Nathan L.R.; Siboni, Nachshon; McLellan, Sandra L.; Potts, Jaimie; Scanes, Peter; Johnson, Colin; James, Melanie; McCann, Vanessa; Seymour, Justin R.
Abstract: Anthropogenic waste streams can be major sources of antibiotic resistant microbes within the environment, creating a potential risk to public health. We examined patterns in the occurrence of a suite of antibiotic resistance genes (ARGs) and their links to enteric bacteria at a popular swimming beach in Australia that experiences intermittent contamination by sewage, with potential points of input including stormwater drains and a coastal lagoon. Samples were collected throughout a significant rainfall event (40.8 mm over 3 days) and analysed using both qPCR and 16S rRNA amplicon sequencing. Before the rainfall event, low levels of faecal indicator bacteria and a microbial source tracking human faeces (sewage) marker (Lachno3) were observed. These levels increased over 10x following rainfall. Within lagoon, drain and seawater samples, levels of the ARGs sulI, dfrA1 and qnrS increased by between 1 and 2 orders of magnitude after 20.4 mm of rain, while levels of tetA increased by an order of magnitude after a total of 40.8 mm. After 40.8 mm of rain sulI, tetA and qnrS could be detected 300 m offshore with levels remaining high five days after the rain event. Highest levels of sewage markers and ARGs were observed adjacent to the lagoon (when opened) and in-front of the stormwater drains, pinpointing these as the points of ARG input. Significant positive correlations were observed between all ARGs, and a suite of Amplicon Sequence Variants that were identified as stormwater drain indicator taxa using 16S rRNA amplicon sequencing data. Of note, some stormwater drain indicator taxa, which exhibited correlations to ARG abundance, included the human pathogens Arcobacter butzleri and Bacteroides fragilis . Given that previous research has linked high levels of ARGs in recreationally used environments to antimicrobial resistant pathogen infections, the observed patterns indicate a potentially elevated human health risk at a popular swimming beach following significant rainfall events. Graphical abstract: Image 1 Highlights: Levels of human sewage markers were elevated during rainfall. Levels of ARGs correlated significantly with markers for human sewage. Not all ARGS displayed the same spatiotemporal distribution patterns. ARGs significantly correlated with stormwater drain indicator bacteria. Some ARGs were correlated with known human pathogens.